Growth differentiation factor 7 alleviates the proliferation and metastasis of hepatocellular carcinoma - Jianyong Zhuo; Huigang Li; Peiru Zhang; Chiyu He; Wei Shen; Xinyu Yang; Zuyuan Lin; Runzhou Zhuang; Xuyong Wei; Shusen Zheng; Xiao Xu; Di Lu (Liver Research)
Background and aims: Inflammatory factors play significant roles in the development and occurrence of hepatocellular carcinoma (HCC). However, the tumor-protective functions of growth differentiation factors (GDFs) in HCC are yet to be clarified. In this study, we aimed to evaluate the expression levels of 10 GDFs in tumor and paratumor tissues from patients with HCC and perform in vitro and in vivo experiments to elucidate the role of GDF7 in regulating the proliferation and metastasis of HCC. Methods: The gene expression of 10 GDFs was compared between HCC and paratumors using The Cancer Genome Atlas dataset and patient-derived tissues. A tumor microarray containing 108 HCC tissue samples was used to explore the prognostic value of GDF7 expression. Loss-of-function experiments were also performed in vitro and in vivo to investigate the role of GDF7 in HCC. Results: The mRNA and protein levels of GDF7 were significantly lower in HCC tumors than in paratumors (P < 0.001). Kaplan–Meier analysis showed that decreased GDF7 expression in HCC was associated with worse overall survival (5-year rate: 61.8% vs. 27.5%, P < 0.001) and increased recurrence risk (P < 0.001). Multivariate Cox regression analysis demonstrated that low GDF7 expression, the presence of microvascular invasion, and elevated alpha-fetoprotein (AFP) levels were independent risk factors for tumor recurrence and poor survival. Downregulation of GDF7 also increased the tumor growth in HCC cells and in an HCC xenograft model. GDF7 knockdown promoted migration and invasion via epithelial–mesenchymal transition. Meanwhile, a negative correlation between JunB proto-oncogene (JUNB) and GDF7 was observed in HCC tissues. Modulating JUNB levels altered GDF7 protein expression. Conclusions: GDF7 is a potential biomarker for predicting superior outcomes in patients with HCC. GDF7 amplification is a potential therapeutic option for HCC.